Social-cognitive antecedents of hand washing: Action control bridges the planning–behaviour gap - Reyes Fernández, Benjamín (2016)
Objectives. To examine motivational and volitional factors for hand washing in young adults, using the Health Action Process Approach (HAPA) as a theoretical framework. Design. In a longitudinal design with two measurement points, six weeks apart, university students (N = 440) completed paper-based questionnaires. Main outcome measures. Prior hand washing frequency, self-efficacy, outcome expectancies, intention and action planning were measured at baseline, and coping planning, action control and hand washing frequency were measured at follow-up. Results. A theory-based structural equation model was specified. In line with the HAPA, the motivational factors of self-efficacy and outcome expectancies predicted intention, whereas the volitional factors of planning and action control mediated between intention and changes in hand washing frequency. Action control was confirmed as the most proximal factor on hand washing behaviour, thus representing a bridge of the planning–behaviour gap. Conclusions. Both motivational and volitional processes are important to consider in the improvement of hand hygiene practices. Moreover, the statistically significant effects for planning and action control illustrate the importance of these key self-regulatory factors in the prediction of hand hygiene. The current study highlights the importance of adopting models that account for motivational and volitional factors to better understand hand washing behaviour.